Pengaruh Kompetensi dan Lingkungan Kerja terhadap Kinerja Karyawan Melalui Motivasi Kerja sebagai Variabel Intervening pada Divisi Produksi PT. XYZ Tbk Bogor - Abdul Rahman Nulhakim; Sudarijati Sudarijati; Palahudin Palahudin (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to determine employee responses and to analyze the direct and indirect influence of competence and work environment on employee performance through work motivation as an intervening variable in the production division of PT. XYZ Tbk Bogor. The number of samples in this study was 78 people using probability sampling techniques. This research uses path analysis data analysis techniques. Testing the data using the SPSS program version 22. The results showed that the employee's response to performance and competence was in the very good category, and the employee's response to the work environment and work motivation was included in the good category. Meanwhile, the results of hypothesis testing prove that competence and work environment have a direct and significant effect on work motivation. Competence, work environment and work motivation have a direct and significant effect on employee performance. Meanwhile, competence and work environment indirectly have no significant effect on employee performance through work motivation as an intervening variable.